2010
DOI: 10.1002/jcp.22105
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions involving IKKγ (NEMO) that promote the activation of NF‐κB

Abstract: Inhibitor of kappaB kinase (IKK) gamma (IKKgamma), also referred to as nuclear factor kappaB (NF-kappaB) essential modulator (NEMO), is an important regulatory component of the IKK complex. The IKK complex is a signalosome that catalyzes the inducible phosphorylation of IkappaB proteins, which is a key step that leads to the activation of NF-kappaB. The exact functions of IKKgamma (NEMO) as part of the IKK complex have not yet been fully elucidated. This mini-review covers 16 proteins that have been reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…RhoA-RhoGDI Complex Binds to IKK␥ Allowing RhoA Activation-Generally, IKK␥ provides binding sites for many proteins; 16 proteins have been reported as directly binding to IKK␥ and promoting the activation of NF-B (38). Here, we presented that RhoA-GDP and RhoGDI are also bound to IKK␥; RhoA-GDP was bound to the N-terminal domain (aa and RhoGDI was bound to the large C-terminal domain (estimated aa 112-419) of IKK␥.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA-RhoGDI Complex Binds to IKK␥ Allowing RhoA Activation-Generally, IKK␥ provides binding sites for many proteins; 16 proteins have been reported as directly binding to IKK␥ and promoting the activation of NF-B (38). Here, we presented that RhoA-GDP and RhoGDI are also bound to IKK␥; RhoA-GDP was bound to the N-terminal domain (aa and RhoGDI was bound to the large C-terminal domain (estimated aa 112-419) of IKK␥.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway seems to be independent of NEMO activity (1). Recent publications have also shown that diverse posttranslational modifications, including ubiquitination, sumoylation, and phosphorylation, regulate the function of NEMO in the IKK complex (2)(3)(4)(5)(6).…”
mentioning
confidence: 93%
“…Two distinct pathways of NF-B activation have been reported. The classical, canonical pathway is found in virtually all mammalian cells and depends on the presence of the IKK␥/NF-B essential modulator (NEMO) 3 protein (1). In this pathway, NF-B activation is mediated by the IKK complex, consisting of the IKK1/IKK␣ and IKK2/IKK␤ catalytic kinase subunits and the NEMO regulatory protein (1).…”
mentioning
confidence: 99%
“…NF-κB is a multi-functional nuclear transcription factor, and is associated with the LPS-induced inflammatory response (19). In the cytoplasm, IκB binds with inactive NF-κB, which covers the nuclear localization sequence of NF-κB and thus prevents the activation and nuclear translocation of NF-κB (20). IκB degradation is therefore required for the activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%